Heritage of Islamic Civilization in Persia Era of Shah Abbas I (1588-1629 CE) - Ahdillah, Zaahidah Aufaa; Sari, Ainun Nuriyah Rahmah; Hernawan, Wawan; Kusdiana, Ading (PT. Student Rihlah Indonesia, 2025)
This study analyzes the cultural heritage of Islamic civilization in Persia during Shah Abbas I’ reign (1588-1629 CE), focusing on the interplay between political power, religious identity, and cultural expression. Using a historical research method (heuristics, criticism, interpretation, and historiography), and an interdisciplinary lens, the study addresses gaps in the literature by combining art historical, political, and social perspectives. The results show that monumental architecture (Imam Mosque, Meidan Emam), textile arts, and economic policies were not only artistic achievement but also tools for legitimizing Safavid rule and reinforcing Shia identity. Isfahan, as the capital, exemplified integration between religion, economy, and culture, supporting the dynasty’s political stability. This cultural legacy later shaped modern Iranian national identity. This research contributes to the dynamic understanding of Islamic civilization and the relevance of cultural heritage in the contemporary context. The implications of this research encourage the preservation of cultural heritage as an instrument of diplomacy and inclusive history education. The study's originality lies in its holistic approach combining material and non-material analysis, distinguishing it from previous partial studies.